STUDENTS ENTREPRENEURSHIP INTENTION IN METROPOLITAN AND INDONESIA FREE TRADE ZONE: IS IT DIFFERENT? - Prakoso, Albrian Fiky; Soesatyo, Yoyok; Kurniawan, Riza Yonisa (Information Management and Business Review, 2020)
This study aims to determine the Entrepreneurship Intention of students in Universitas Negeri Surabaya (Unesa) which is a metropolitan area and Riau Islands University (Unrika) in Indonesia Free Trade Zone. To distinguish Entrepreneurship Intention from students in this study using Theory of Planned Behavior (TPB). This type of research is quantitative exploratory research. Data analysis using Structural Equation Modeling (SEM) with the WarpPLS approach. Respondents in this study are Unesa and Unrika students, 6th-semester Economics or had taken entrepreneurship courses with a total of 142 students. There are similar intentions of Unrika entrepreneurship with Unesa. In Unrika, they were in the free trade zone area so they were more consumptive towards electronics because of their low price and reluctant to be entrepreneurs. In the free trade zone, if we want to sell an item outside the island, it will be charged by the gonverment, and the price will be same like the price from the outside of free trade zone. Moreover, most of their parents are workers or civil servants and not entrepreneurs. The cause of Unesa students is reluctant to become entrepreneurs because most of them want to become civil servants based on the influence of the family environment which on average comes from the village and works as a civil servant. For Unrika, most of them are college workers, so their mindset before and when they are studying is as workers.